Biodiversity and ecosystem multifunctionality. - Hector, A; Bagchi, R (2007)
Biodiversity loss can affect ecosystem functions and services. Individual ecosystem functions generally show a positive asymptotic relationship with increasing biodiversity, suggesting that some species are redundant. However, ecosystems are managed and conserved for multiple functions, which may require greater biodiversity. Here we present an analysis of published data from grassland biodiversity experiments, and show that ecosystem multifunctionality does require greater numbers of species. We analysed each ecosystem function alone to identify species with desirable effects. We then calculated the number of species with positive effects for all possible combinations of functions. Our results show appreciable differences in the sets of species influencing different ecosystem functions, with average proportional overlap of about 0.2 to 0.5. Consequently, as more ecosystem processes were included in our analysis, more species were found to affect overall functioning. Specifically, for all of the analysed experiments, there was a positive saturating relationship between the number of ecosystem processes considered and the number of species influencing overall functioning. We conclude that because different species often influence different functions, studies focusing on individual processes in isolation will underestimate levels of biodiversity required to maintain multifunctional ecosystems.